2021
DOI: 10.1016/j.stemcr.2021.10.014
|View full text |Cite
|
Sign up to set email alerts
|

In vitro expanded skeletal myogenic progenitors from pluripotent stem cell-derived teratomas have high engraftment capacity

Abstract: Summary One major challenge in realizing cell-based therapy for treating muscle-wasting disorders is the difficulty in obtaining therapeutically meaningful amounts of engraftable cells. We have previously described a method to generate skeletal myogenic progenitors with exceptional engraftability from pluripotent stem cells via teratoma formation. Here, we show that these cells are functionally expandable in vitro while retaining their in vivo regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…We previously reported that in vivo PSC differentiation from both mouse and human PSCs produced skeletal myogenic progenitors that were both engraftable and expandable (Chan et al, 2018; Pappas et al, 2022; Xie et al, 2021; Xie et al, 2023). These in vivo differentiated skeletal myogenic progenitors had excellent muscle regeneration potency upon transplantation and could produce new fibers to a similar extent as adult MuSCs (Chan et al, 2018; Xie et al, 2021). Remarkably, in vivo differentiated skeletal myogenic progenitors could be cultured and expanded in vitro over several passages while still retaining their outstanding engraftability (Xie et al, 2021; Xie et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously reported that in vivo PSC differentiation from both mouse and human PSCs produced skeletal myogenic progenitors that were both engraftable and expandable (Chan et al, 2018; Pappas et al, 2022; Xie et al, 2021; Xie et al, 2023). These in vivo differentiated skeletal myogenic progenitors had excellent muscle regeneration potency upon transplantation and could produce new fibers to a similar extent as adult MuSCs (Chan et al, 2018; Xie et al, 2021). Remarkably, in vivo differentiated skeletal myogenic progenitors could be cultured and expanded in vitro over several passages while still retaining their outstanding engraftability (Xie et al, 2021; Xie et al, 2023).…”
Section: Resultsmentioning
confidence: 99%
“…We subsequently cultured isolated α7-Integrin + VCAM + cells in myogenic medium with or without LIF (1000 units/mL) for 12 days over 3 passages. Untreated and LIF-treated passage 3 MuSC cultures were then transplanted at 40,000 cells/muscle into the TA muscles of NSG-mdx 4Cv mice, a DMD model we have previously used to evaluate cell transplantation success (Arpke et al, 2013; Chan et al, 2018; Xie and Chan, 2023; Xie et al, 2021; Xie et al, 2023). Four weeks later, the transplanted muscles were harvested for fiber engraftment evaluation, as defined by donor-derived DYSTROPHIN + fibers (recipient mice lack dystrophin in their muscles).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, major obstacles in the clinic are the large cell numbers required for transplantation and the fact that ex vivo amplification of trunk MuSCs leads to a drastic decline in regenerative potential due to commitment to differentiation (Briggs and Morgan, 2013; Ikemoto et al, 2007). Substantial advances have been made by modifying the MuSC culture conditions (Charville et al, 2015; L’honoré et al, 2018), or by the use of teratoma-derived skeletal myogenic progenitors (Xie et al, 2021). As such, the identification of factors that regulate cell fate decisions in distinct MuSC populations serves as a resource for advancing knowledge in the context of regenerative medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Due to these difficulties, other sources of cells, for example stem cells, have been considered [ 5 ]. Some of them, such as pluripotent stem cells (PSCs), are undoubtedly characterized by myogenic potential, as they can convert into skeletal muscle tissue during teratoma or chimera formation [ 6 , 7 , 8 , 9 ]. They were also shown to be able to differentiate into functional SCs during in vitro culture when exposed to myogenic regulators, such as WNT, BMP4 inhibitor, FGF2, or when factors crucial for embryonic myogenesis were overexpressed in these cells [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%